Initial Parameters Affecting the Multilayer Doubly Curved Concrete Shell Roof - Thi My Dung Do; Thanh Quang Khai Lam; Thi Thu Nga Nguyen; Van Thuc Ngo; Hoang Hung Vu; Trong Chuc Nguyen; Van Duan Doan (Advances in Civil Engineering)
Doubly curved shell roof structures have been widely studied and applied in civil buildings, because of their compressive capacity. As a spatial structure, it should increase the space, reduce the thickness of the shell, and create the architecture for the building. In particular, reinforcement is needed to repair the shell surface, forming the multilayer curved shell roof structures. In this multilayer curved shell roof, it is necessary to investigate the influence of thickness of layers, the influence of the location of the steel fibres concrete layer, and the influence of steel fibres content contained in concrete on the state of stress and strain and build relationships, load-vertical displacement and stress in the x and y directions of the shell in the investigated cases. So, this paper presents an ANSYS numerical simulation study related to the state of stress and strain in double-layer doubly curved concrete shell roof with the initial parameters being changed such as the thickness of the layers, the location of the steel fibres concrete layer in the structure (the steel fibres concrete layer that is placed above and below the normal concrete layer), and the steel fibres content contained in concrete shell with the size of 3000 × 3000 mm, which is simulated by ANSYS after being experimentally conducted on this curved shell roof; the results of experimental and simulation study are verified by each other. Research results show that the thickness of the steel fibres concrete layer is placed below the normal concrete layer, the percentage of steel fibres contained in the concrete is 2%, and the bearing capacity of the curved shell is optimal.